The complete chloroplast genome of Agrostis capillaris L. Issue 9 (2nd September 2021) - He, Hongyan; Fu, Jiayi; Wang, Qianqian; Xi, Qianqian; Wei, Xiangyu; Zhao, Yi; Ling, Chen; Chang, Tianliang; Zhao, Yuwei
Abstract: Agrostis capillaris is a cool-season turf grass species that is found worldwide in temperate countries, and a good Pb phytostabilizer. In this study, the entire chloroplast genome sequence of A. capillaris was determined by Illumina sequencing. The complete chloroplast genome was circular and composed of 136, 396 bp nucleotides with a GC content of about 38.5%. There were a large single-copy region (LSC, 81, 659bp), a small single-copy region (SSC, 12, 593bp), and a pair of reverse repeat regions (IRs, 42, 144bp) in the chloroplast genome. In total, the A. capillaris chloroplast genome contained 144 genes, including 96 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. Phylogenetic analysis revealed that A. capillaris was closely related to A. gigantean . The sequence data of A. capillaris chloroplast genome could provide useful genetic information for the studies on phylogenetic and evolutionary of Agrostidinae.